Analisis Fikih Kontemporer dan Undang-Undang Agraria terhadap Penyelesaian Konflik Sengketa Tanah di Kabupaten Bulukumba - Fitri, Sakinah; Mustari, Abdillah; Kurniati, Kurniati (Universitas Islam Negeri Alauddin Makassar, 2024)
This research presents three problem formulation items, namely: First, what are the dynamics of land dispute conflicts between PT. Lonsum and the Community in Tamatto Village, Ujungloe District, Bulukumba Regency? Second, how can contemporary fiqh approaches be applied in resolving land disputes between PT. Lonsum and the Tamatto Village Community? Third, how is the implementation of Agrarian law in resolving land disputes between PT. Lonsum and the Community of Tamatto Village, Ujungloe District, Bulukumba Regency? This research is a qualitative study that uses two data collection methods. First, through primary approaches such as observation, interviews and documentation. Second, using a secondary approach such as library research through books, journals, theses, annual reports and internet sites that are relevant to the research topic. The results of this research illustrate two main things: First, the dynamics of land dispute conflicts began when PT. Lonsum widened land that was not included in its Cultivation Rights land, so the widening caused the community to sue the company, but in suing the community, they did not have a land certificate for the land they claimed, so the land dispute has not yet been resolved. Second, the Contemporary Jurisprudence Approach is applied using wasatiyyah (the principle of balance) by finding solutions without taking sides against one party and respecting the interests of both parties by applying the concept of justice and trying to reconcile both parties. Third, non-litigation settlement of agrarian laws (outside of court), through mediation, in this case the government mediates, facilitates and brings together the two parties. In this meeting, there was a bright spot/solution that was applied to the dispute that occurred. Effective communication is the main key in resolving conflict. By communicating well, it is hoped that the best solution will be found. The government has a role as a mediator between companies and society in this matter. It is important for the government to be fair and neutral without taking sides with one party. Resolving this conflict requires the government to take firm steps that are balanced between both parties.